Genetic and Epigenetic Defects at the GNAS Locus Lead to Distinct Patterns of Skeletal Growth but Similar Early‐Onset Obesity. (7th June 2018) - Hanna, Patrick; Grybek, Virginie; Perez de Nanclares, Guiomar; Tran, Léa C; de Sanctis, Luisa; Elli, Francesca; Errea, Javier; Francou, Bruno; Kamenicky, Peter; Linglart, Léa; Pereda, Arrate; Rothenbuhler, Anya; et al.
ABSTRACT: Pseudohypoparathyroidism type 1A (PHP1A), pseudoPHP (PPHP), and PHP type 1B (PHP1B) are caused by maternal and paternal GNAS mutations and abnormal methylation at maternal GNAS promoter(s), respectively. Adult PHP1A patients are reportedly obese and short, whereas most PPHP patients are born small. In addition to parathyroid hormone (PTH) resistance, PHP1A and PHP1B patients may display early‐onset obesity. Because early‐onset and severe obesity and short stature are daily burdens for PHP1A patients, we aimed at improving knowledge on the contribution of the GNAS transcripts to fetal and postnatal growth and fat storage. Through an international collaboration, we collected growth and weight data from birth until adulthood for 306 PHP1A/PPHP and 220 PHP1B patients. PHP1A/PPHP patients were smaller at birth than healthy controls, especially PPHP (length Z ‐score: PHP1A –1.1 ± 1.8; PPHP –3.0 ± 1.5). Short stature is observed in 64% and 59% of adult PHP1A and PPHP patients. PHP1B patients displayed early postnatal overgrowth (height Z ‐score at 1 year: 2.2 ± 1.3 and 1.3 ± 1.5 in autosomal dominant and sporadic PHP1B) followed by a gradual decrease in growth velocity resulting in normal adult height ( Z ‐score for both: –0.4 ± 1.1). Early‐onset obesity characterizes GNAS alterations and is associated with significant overweight and obesity in adults (bodey mass index [BMI] Z ‐score: 1.4 ± 2.6, 2.1 ± 2.0, and 1.4 ± 1.9 in PPHP, PHP1A, and PHP1B, respectively), indicating that reduced Gsα expression is a contributing factor. The growth impairment in PHP1A/PPHP may be due to Gsα haploinsufficiency in the growth plates; the paternal XLαs transcript likely contributes to prenatal growth; for all disease variants, a reduced pubertal growth spurt may be due to accelerated growth plate closure. Consequently, early diagnosis and close follow‐up is needed in patients with GNAS defects to screen and intervene in case of early‐onset obesity and decreased growth velocity. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research (ASBMR).